Pulmonary Embolism Successfully Treated with Tenecteplase: A case report (Bangladesh Heart Journal, 2023)
Acute pulmonary embolism is a life-threatening situation when presenting with hypotension is called high-risk (massive) pulmonary embolism (PE) which is associated with mortality, especially if there is hemodynamic instability, right ventricular dysfunction with thrombus. Thrombolytic therapy can be lifesaving and leads faster improvement in hemodynamics in patients with acute pulmonary embolism and cardiogenic shock which accelerates the resolution of thrombus, reduction of RV dilatation, mortality and recurrent PE. Only three fibrinolytic agents namely Recombinant tissue-type plasminogen activator (rtPA), Streptokinase and Urokinase have been approved in the treatment of PE. We report the case of a 64 years old Bangladeshi female with a history of immobilization due to unilateral cut injury of foot, who presented with shortness of breath and intermittent chest pain for a duration of 7 days during OPD visit. ECG showed sinus tachycardia (HR-120bpm, regular) and poor progression of R wave. Echocardiography revealed dilated RV, PA with RV dysfunction, presence of McConnell’s sign, RV apical & PA thrombus, flattened IVS, PHT, and minimal pericardial effusion, normal LV systolic function which was reported as suspected pulmonary embolism. Urgent hospitalization and CT pulmonary angiogram (CTPA) was done for confirmatory diagnosis which revealed large pulmonary thrombus in both right and left pulmonary artery. Thrombolysis with Tenecteplase (100ml) over 2 hours was started immediately along with intravenous normal saline and norepinephrine for hypotension, although, it was not recommended by the European Society of Cardiology (ESC) guideline, resulting a successful resolution of the PA thrombus and clinical improvement. She was discharged with oral anticoagulant Rivaroxaban. Bangladesh Heart Journal 2023; 38(2): 148-154